Management of white spot lesions by resin infiltration: a case series - Liangyue Pang; Qinghui Zhi (Frontiers in Oral Health, 2026)
White spot lesions (WSLs) present as color abnormalities on the tooth surface and represent early signs of demineralization beneath intact enamel, potentially affecting patients’ aesthetics and self-confidence. Management strategies for WSLs include remineralization using casein phosphopeptide–amorphous calcium phosphate (CPP-ACP) pastes or topical fluoride applications, microabrasion with an 18% hydrochloric acid and pumice mixture, and resin infiltration. Resin infiltration is a minimally invasive aesthetic treatment for WSLs, though multiple factors may influence the final aesthetic outcome. This paper reports three cases of white spot lesions treated with resin infiltration and discusses the factors that may affect treatment efficacy. Clinical Relevance Resin infiltration is a clinically effective method for caries lesions classified as ICDAS 2–3. While white spot lesions can be treated with resin infiltration, not all cases achieve satisfactory aesthetic results. Successful implementation requires careful case selection, adherence to standardized protocols, and appropriate follow-up.